Active proton secretion and potassium absorption in the rabbit outer medullary collecting duct. Functional evidence for proton-potassium-activated adenosine triphosphatase. - Wingo, C S (1989)
We examined the hypothesis that proton-potassium-activated adenosine triphosphatase (H-K-ATPase) mediates K absorption and acidification in the inner stripe of the outer medullary collecting duct (OMCDi). Rabbits were fed a low-K diet (0.55% K) for 7-14 d because we have demonstrated previously that this low-K diet stimulates K-absorptive flux by the OMCDi. Proton secretion was measured as net total CO2 flux (JTCO2) by microcalorimetry. After basal collections, either vehicle or an inhibitor of gastric H-K-ATPase, omeprazole (0.1 mM), was added to the perfusate during the second period. Addition of vehicle to the perfusate changed neither the transepithelial voltage (VT, in millivolts) nor the JTCO2. In contrast, the addition of omeprazole (0.1 mM) to the perfusate abolished JTCO2 (from 14.5 +/- 5.6 to -0.1 +/- 3.1 pmol.mm-1.min-1) without significantly affecting VT. In additional experiments, in 16 tubules there was significant net K absorption (JK) of 5.0 +/- 1.0 pmol.mm-1.min-1 during the basal period, which exceeded the rate of K absorption that could be attributed to a paracellular voltage-mediated pathway (JKP = 1.0 +/- 0.4 pmol.mm-1.min-1, P less than 0.01). Administration of vehicle did not significantly affect either VT or JK. However, omeprazole abolished JK (from 5.1 +/- 1.0 to 0.1 +/- 2.5 pmol.mm-1.min-1) without affecting VT or JNa. The present results demonstrate that the OMCDi possesses an active, omeprazole-sensitive acidification and K-absorptive mechanism. These findings are consistent with the presence of H-K-ATPase activity in this nephron segment.